Juice from solar concentrate [photovoltaic collector]. - Patel-Predo, P. (IEEE spectrum)
Conventional photovoltaic (PV) panels made from silicon to provide electricity to office buildings and homes are still too expensive. Unless they are heavily subsidized, it rarely makes sense to install them where electricity is available from the grid. This paper discusses a new type of photovoltaic collector developed by New York state's interdisciplinary team. The key element in their design is a concentrator with a Fresnel lens, whose concentric grooves focus light on a postage stamp-size cell made of gallium arsenide.